Riemersioni vittoriniane su una «rivista impossibile-possibile» - Zamboni, Isabel (L’ospite ingrato, 2025)
Thanks to the discovery of a letter from Elio Vittorini to Francesco Leonetti, this essay aims to reconstruct the role played by the two writers in conceiving the international journal «Il Gulliver». Particular attention is devoted to their relationship with Einaudi, identified as the editorial referent in Italy, and to the preparation of the seventh issue of «Il Menabò», in which the preparatory materials of the international journal were published.